The Use of ICT in the Implementation of Autonomous Learning: Students’ Perception - Anindya, Widya Dara; Lusiyani, Ria (Social Sciences, Humanities and Education Journal (SHE Journal), 2024)
This qualitative study investigates how students use ICT to support their independent learning in English. The participants of this study were 5th-semester students who were taking the Cross-Cultural Understanding subject, totaling 117 students. The data were collected using a questionnaire via Google Form and distributed in the first week of the CCU lectures. This study has two main findings. The first finding concerns the applications used in implementing independent learning, categorized into five categories: chat and messages, social media, online games, learning apps, and others. The second finding focuses on the activities conducted by students in their independent learning. The questionnaire results identified twenty activities grouped into five categories: listening, writing, speaking, reading, and others. Furthermore, listening was the most frequently reported activity among students in independent learning